Slope Stability for Landslide in Road Preservation Working Packages Ende-Wolowaru and Junction-Kelimutu STA 8+425 - Sasarari, Frans Andre; Lastiasih, Yudhi; Wahyudi, Herman; Junianto, Agustinus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
On the Ende-Kelimutu national road section at STA 8+425, according to the identification and field survey, the landslide that occurred at this point was caused by high rainfall intensity and geological factors of the slope. As the road supervisor, the Balai Pelaksanaan Jalan Nasional (BPJN) of East Nusa Tenggara has designed a landslide treatment using a combination of cantilever walls and drilled poles. Soil investigation data at STA 8+425 shows that the slope is dominated by sand with N-SPT values above 15 to a depth of 14.45 meters. When making design improvements, a number of rainfall data from several weather observation stations are needed, in order to determine the effect of rainwater infiltration on the landslides that occur. This study aims to determine the influence of rainwater infiltration on the occurrence of landslides at the study site, where the results of the analysis conducted with Geostudio prove the truth. Modeling with the combination of SEEP/W and SLOPE/W, the FS value before the landslide was 2.302 and then decreased to 0.35 during the landslide.